دور العقار الاقتصادي في جذب الاستثمار - سراي تقي الدين (جامعة المسيلة, 2025)
This study aimed to determine the role that the economic property is entrusted in providing and creating an investment climate, in addition to trying to unveil the strategy of the Algerian legislator in attracting and attracting national investments from it and foreign, by relying on the descriptive approach to introduce concepts under study, as well as the deductive approach based on the generalization towards allocation, and the use of analysis as a tool to dismantle legal texts, where through the above This study carried many results, including that the economic property exceeds that it is just a ground on which investment projects are established, but rather it has economic, social and even political dimensions, and the Algerian legislator's strategy in organizing and conducting the economic real estate appears in accordance with legal, administrative and technical standards, and among the proposals we have registered we mention avoiding the focus of investment projects in some states, especially those that witness an increasing demand, and grant the private sector More freedom in the process of organizing and running the economic real estate, and these policies will enhance the investment movement in Algeria.
Keywords: Economic real estate; Investment climate; Attracting investments.